Exploring core and bridge symptoms in patients recovering from stroke: a network analysis - Huang, Yao; Cao, Songmei; Li, Teng; Wang, Jingjing; Xia, Zhuoran (Frontiers in Neurology, 2024)
Background Patients recovering from stroke experience a variety of symptoms that present as a synergistic and mutually reinforcing “symptom cluster,” rather than as singular symptoms. In this study, we researched and systematic analyzed these symptom clusters, including core and bridge symptoms, to help determine the relationships between symptoms and to identify key symptom targets, providing a new approach for formulating precise symptom management interventions. Methods Convenience sampling was applied to select 432 stroke recovery patients treated in the Seventh People’s Hospital of Changzhou City from August 1, 2023 to April 14, 2024. Subsequently, a cross-sectional survey was conducted using the General Information Questionnaire and Stroke Symptom Experience Scale to extract symptom clusters via exploratory factor analysis. Finally, the “qgraph” and “bootnet” packages in the R language were used to construct a network layout to describe the relationships between symptoms and calculate the centrality index. Results The average age of the 432 enrolled recovering stroke patients was 68.17 ± 12.14 years, including 268 males (62.04%) and 164 females (37.96%), none of whom underwent surgical intervention. Among this cohort, the 3 symptoms with the highest incidence rates were “limb weakness” (A2, 80.56%), “fatigue” (A5, 77.78%), and “limitations of limb movement” (A1, 68.06%). A total of 5 symptom clusters were extracted: the somatic activity disorder, mood-disorder-related, cognitive–linguistic dysfunction, somatic-pain-related, and foot dysfunction symptom clusters. In the symptom network, the 2 most common symptoms in terms of intensity and expected impact were “fatigue” (A5, rs = 1.14, re = 1.00) and “pessimism about the future” (B3, rs = 1.09, re = 1.02). The symptom with the strongest bridge intensity was “limb pain” (D1, rs = 2.64). Conclusion This study uses symptom network analysis to explore the symptoms of stroke patients during recovery, identifying core symptoms and bridge symptoms. Based on these findings, we can develop more targeted management plans to improve the accuracy and efficiency of interventions. Through this management approach, we can enhance treatment effectiveness, reduce unnecessary medication, lower adverse drug reactions, and optimize the allocation of medical resources.